AI-Powered Smart Classrooms for C-PBL: Enhancing Mobile and Virtual Learning Technologies - Rattanakha, Raweewarn; Chatwattana, Pinanta; Piriyasurawong, Pallop (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The AI-powered smart classrooms for C-PBL to enhance mobile and virtual learning technology, or C-PBL mobile and virtual learning are based on the integration of artificial intelligence and virtual reality technologies with problem-based learning and cooperative learning with an attempt to enhance students’ analytical thinking and curiosity. Thereby, students are encouraged to do activities in small groups and use analytical thinking skills to distinguish problems in a systematic manner, which is believed to enable them to create their own bodies of knowledge from the problem-solving process in those situations or problems. The results of this research are consistent with the hypotheses, as it is found that the C-PBL mobile and virtual learning system is considered a learning tool that can be practically applied in cooperative problem-based learning processes through virtual smart classrooms in order to promote students’ analytical thinking and curiosity in learning. Meanwhile, it is believed that the C-PBL mobile and virtual learning system herein also enables students not only to create their own bodies of knowledge after doing small-group activities in virtual environments but also to receive brand-new knowledge as to their own abilities from experiential learning. However, there are still some research gaps in this study that need to be further addressed in the future. For instance, future studies should explore a wider scope of application by doing surveys with more varied populations and broader educational environments so as to confirm the validity and clarity of study results. Therefore, the findings in this study are considered merely the findings derived from a pilot study and can be used as just a guideline for future development.